PENGELOLAAN SARANA DAN PRASARANA TERHADAP KUALITAS LAYANAN PENDIDIKAN - Nurfadillah Ramadhani, Zahwa; Rahmadani, Olivia; Maula Asy-Syifa, Nadiyya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The management of educational facilities and infrastructure and its role in improving the quality of educational services are the focus of this study. Educational facilities and infrastructure are important components that support the effectiveness of the learning process and the quality of services received by students. This study aims to analyze the stages of facilities and infrastructure management, which include planning, procurement, utilization, maintenance, and supervision, as well as their implications for educational service quality. The research method used is library research by reviewing various relevant reference books and scientific journal articles. Data were collected through documentation techniques and analyzed using descriptive qualitative analysis with a content analysis approach. The findings indicate that planned, integrated, and sustainable management of educational facilities and infrastructure contributes positively to improving the quality of educational services, particularly in terms of learning comfort, service effectiveness, and student satisfaction. Therefore, the management of educational facilities and infrastructure should be viewed as a strategic component in efforts to improve educational service quality.